Role of mesenchymal stem cells in the pathogenesis of psoriasis: current perspectives - Campanati, Anna (Psoriasis (Auckl), 2017)
Mesenchymal stem cells (MSCs) are multipotent nonhematopoietic stromal cells studied for their properties and importance in management of several skin diseases. This review collects and analyzes the emerging published data, which describe the function of MSCs in the pathogenesis of psoriasis.